2009
DOI: 10.2478/s11756-009-0133-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in feeding selectivity and efficiency between young-of-the-year European perch (Perca fluviatilis) and roach (Rutilus rutilus) — field observations and laboratory experiments on the importance of prey movement apparency vs. evasiveness

Abstract: Differences in feeding selectivity and efficiency between young-of-the-year European perch (Perca fluviatilis) and roach (Rutilus rutilus) -field observations and laboratory experiments on the importance of prey movement apparency vs. evasiveness Jiří Peterka & Josef MatěnaBiology Centre of the Academy of Sciences of the Czech Republic, Institute of Hydrobiology, Na Sádkách 7, CZ-37005 České Budějovice, and Faculty of Science, University of South Bohemia, Branišovská 31, CZ-37005 České Budějovice, Czech Republ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 33 publications
2
23
2
Order By: Relevance
“…The most significant changes in roach food composition are found in steep-sided canyon-shaped valley reservoirs, Roach diet in a reservoir 19 68.9 ± 12.7 189.4 ± 63.9 63.7 ± 24.6 222.2 ± 73.1 35.7 ± 13.2 122.1 ± 17.6 38.2 ± 11.4 185.1 ± 65.5 Hammer (1985), Ponton and Gerdeaux (1988), Giles et al (1990), and Peterka and Matěna (2009) all found roach to specialise in feeding on crustacean zooplankton at such sites only Richeux et al (1992) found, by contrast, in the deep lake of Pareloup (Massif Central, France) that smaller roach (10-21 cm) had a diet chiefly of detritus and zooplankton, whilst oldest individuals were detritivores. While roach typically select zooplankton in deep reservoirs, its ability to feed on detritus may also provide it with an energetic advantage, increasing the carrying capacity for this species in lakes where detritus occurs and is accessible.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant changes in roach food composition are found in steep-sided canyon-shaped valley reservoirs, Roach diet in a reservoir 19 68.9 ± 12.7 189.4 ± 63.9 63.7 ± 24.6 222.2 ± 73.1 35.7 ± 13.2 122.1 ± 17.6 38.2 ± 11.4 185.1 ± 65.5 Hammer (1985), Ponton and Gerdeaux (1988), Giles et al (1990), and Peterka and Matěna (2009) all found roach to specialise in feeding on crustacean zooplankton at such sites only Richeux et al (1992) found, by contrast, in the deep lake of Pareloup (Massif Central, France) that smaller roach (10-21 cm) had a diet chiefly of detritus and zooplankton, whilst oldest individuals were detritivores. While roach typically select zooplankton in deep reservoirs, its ability to feed on detritus may also provide it with an energetic advantage, increasing the carrying capacity for this species in lakes where detritus occurs and is accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Peterka & Matena (2009) demonstrated that prey selection in young-of-the-year roach Rutilus rutilus (Linne) was determined by prey evasiveness. In our study, the movement of jellyfish was restricted because they were tethered by a string.…”
Section: ϫ2mentioning
confidence: 99%
“…The diet and feeding behaviour of perch and roach juveniles has been investigated both in the field and laboratory, and differences in the feeding efficiency for the two most frequent zooplankton taxa i.e. cladocera and copepoda have been reported repeatedly (Winfield et al, 1983;Hammer, 1985;Winfield & Townsend, 1988;Mark et al, 1989;Bergman, 1990;Matěna, 1995;Macháček & Matěna, 1997;Vašek et al, 2006;Peterka & Matěna, 2009). The highest ecological consequences have the findings of Persson (1987), who found juveniles of roach more efficient foragers over perch when feeding on Daphnia sp.…”
Section: Introductionmentioning
confidence: 99%